Fiber Reinforced Bioplastic from Food Waste (Potato peel) - Dr. Pradip K. Wankhade; Fsaha Ahmad; Dhanshree Joshi; Neha Kale (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The bioplastic is an evolution for plastic manufacturing units when conventional plastics use to cause various environmental issues. Biodegradability is an added advantage which can be obtained using bioplastic is that they are produced by renewal resources as a raw material for synthesis. Although, bioplastics may be classified into two types, that are biodegradable and non-biodegradable, depends on the type of plastic which are produced. Whereas, some of the bioplastics are non-biodegradable, the use of biomass in synthesizing the bioplastics will enhance in preserving non-renewable resources, which are inflammable, in producing conventional plastics. However, the mechanical strength of bioplastic still has scope for improvement in comparison with conventional plastics, which is having limited use and its application. Therefore, bioplastics required to be reinforced to improving its performance and properties to get the proper application of it. Synthetic reinforcement has been used to reinforce conventional plastic to achieve its desire properties to get the optimum application. Due to various issues, the trend has been diversified to use natural resources as reinforcements. There are different manufacturing units that have started to use reinforced bioplastic, and this article mainly tries to achieve the advantages of using reinforced bioplastic in various industries and its limitations. Thus, in this paper more emphasis is given to use the natural food waste which is available in ample quantity and possible to prepare the reinforced bioplastic of desired strength and environmentally friendly with biodegradability.